1998
DOI: 10.1089/cap.1998.8.143
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Valproate Concentrations When Coadministered with Guanfacine

Abstract: A preliminary clinical observation suggests the possibility of changes in valproate level when coadministered with guanfacine. Two pediatric inpatients (8 and 9 years of age) were treated with valproic acid and guanfacine concurrently. In one child, when guanfacine was tapered and discontinued, the plasma valproate concentration decreased by 41% from 128 microg/mL to 76 microg/mL. In the other case, studied in an ABA design, the child exhibited a rapid increase in plasma valproate levels while guanfacine was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Other safety concerns with use of concomitant psychotropic medication in youths include 1) the greater possibility of untoward drug interactions (106,107) and 2) the creation of drug-induced behavioral toxicity after the addition of another psychotropic medication-a consequence not often recognized as such, which can then lead to even more complex drug therapy to treat that side effect (100). Table 4 presents a brief list of reports of adverse drug events with the use of concomitant psychotropic medication in youths.…”
Section: Evidence Of Associated Risksmentioning
confidence: 99%
“…Other safety concerns with use of concomitant psychotropic medication in youths include 1) the greater possibility of untoward drug interactions (106,107) and 2) the creation of drug-induced behavioral toxicity after the addition of another psychotropic medication-a consequence not often recognized as such, which can then lead to even more complex drug therapy to treat that side effect (100). Table 4 presents a brief list of reports of adverse drug events with the use of concomitant psychotropic medication in youths.…”
Section: Evidence Of Associated Risksmentioning
confidence: 99%
“…Though there has not been a prior reported association between valproate and hypertensive urgency, it has been shown to cause hypertension [ 2 ]. Studies have linked the significant effects guanfacine can have on valproate metabolism [ 7 ] and the addition of valproate to an already high dose (5 mg total daily dose) of guanfacine that likely led to a rapid increase in valproate levels. Another possible mechanism could be explained by a shared mechanism of action of valproate with carbamazepine, which has been implicated in inducing hypertension [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… 45 In addition, when guanfacine and valproic acid are administered simultaneously, plasma valproate levels may rise significantly. 46 However, two small open-label studies conducted with healthy adults revealed that coadministration of GXR and MPH 47 or lisdexamfetamine 48 did not result in significant pharmacokinetic drug–drug interactions.…”
Section: Pharmacology Of Guanfacinementioning
confidence: 99%